Data from: Microevolutionary selection dynamics acting on immune genes of the green veined white butterfly, Pieris napi - Keehnen, Naomi L.P.; Hill, Jason; Nylin, Sören; Wheat, Christopher W. (Zenodo, 2018)
Insects rely on their innate immune system to successfully mediate complex interactions with their microbiota, as well as the microbes present in the environment. Previous work has shown that components of the canonical immune gene repertoire evolve rapidly and have evolutionary characteristics originating from interactions with fast-evolving microorganisms. Although these interactions are likely to vary among populations, there is a poor understanding of the microevolutionary dynamics of immune genes, especially in non-Dipteran insects. Here we use the full set of canonical insect immune genes to investigate microevolutionary dynamics acting on these genes between and among populations by comparing three allopatric populations of the Green Veined White butterfly, Pieris napi (Lepidoptera, Pieridae). Immune genes showed increased genetic diversity compared to genes from the rest of the genome and various functional categories exhibited different types of signatures of selection, at different evolutionary scales, presenting a complex pattern of selection dynamics. Signatures of balancing selection were identified in 10 genes, and 17 genes appear to be under positive selection. Genes involved with the cellular arm of the immune response as well as the Toll pathway appear to be enriched among our outlier loci, regardless of functional category. This suggests that the targets of selection might focus upon an entire pathway, more than on functional subsets across pathways. Our microevolutionary results are similar to previously observed macroevolutionary patterns from diverse taxa, suggesting that either the immune system is robust to dramatic differences in life history and microbial communities, or that diverse microbes exert similar selection pressures. Piebra_SP_k55b2000_MESPAnapi Draft genome of Pieris brassicae, scaffolded using MESPA. Pool-Seq libraries of the 3 P. napi populations Pool-Seq libraries of Spain: Aiguamolls, Sweden: Abisko, and Sweden: Kullaberg. Stored as NCBI bioproject PRJNA449143. command ...